Permainan Bingo Untuk Menggali Bakat Minat Santri Kelas IX di Madrasah Tsanawiyah - Aprilia, Jessica Fiqma; Khusumadewi, Ari (IAIN Kudus, 2022)
Bingo Game Media to Explore The Aptitudes and Interests of The Third-Grade Students at Mts Nurul Islam Pungging-Mojokerto. The study aims to develop a product in the form of bingo game media to explore the aptitudes and interests of the third-grade students at MTs Nurul Islam Pungging-Mojokerto who met the acceptability criteria. This study uses Borg and Gall's (2008) research and development (R&D) method, which is only carried out until the fifth stage due to limited costs, power, and time. The five stages are research and data collection, planning, develop preliminary form of product, preliminary field testing, and main product revision. The results obtained from the feasibility test are as follows: 1) The assessment of the media expert test is 98.04%, which is included in the very good category and does not need to be revised. 2) The assessment of the material expert test is 82.35%, which is included in the good category and does not need to be revised. 3) The assessment from prospective users is 78.33%, which is included in the good category and does not need to be revised. Based on these data, it can be concluded that the bingo game product to explore talents and interests shows that it has met the acceptability criteria consisting of feasibility, accuracy, usability, and suitabilityKeywords: Aptitude, Interest, Bingo Game Media.